Validation of a Novel Fgf10Cre–ERT2 Knock-in Mouse Line Targeting FGF10Pos Cells Postnatally - Chu, Xuran; Taghizadeh, Sara; Vazquez-Armendariz, Ana Ivonne; Herold, Susanne; Chong, Lei; Chen, Chengshui; Zhang, Jin-San; El Agha, Elie; Bellusci, Saverio (Frontiers in Cell and Developmental Biology, 2021)
Fgf10 is a key gene during development, homeostasis and repair after injury. We previously reported a knock-in Fgf10Cre-ERT2 line (with the Cre-ERT2 cassette inserted in frame with the start codon of exon 1), called thereafter Fgf10Ki-v1, to target Fgf10Pos cells. While this line allowed fairly efficient and specific labeling of Fgf10Pos cells during the embryonic stage, it failed to target these cells after birth, particularly in the postnatal lung, which has been the focus of our research. We report here the generation and validation of a new knock-in Fgf10Cre-ERT2 line (called thereafter Fgf10Ki-v2) with the insertion of the expression cassette in frame with the stop codon of exon 3. This new Fgf10Ki-v2 line exhibited comparable Fgf10 expression levels to wild type animals. However, a mismatch between Fgf10 and Cre expression levels was observed in Fgf10Ki-v2/+ lungs. In addition, lung and limb agenesis were observed in homozygous embryos suggesting a loss of Fgf10 functional allele in Fgf10Ki-v2 mice. Bioinformatic analysis shows that the 3’UTR, where the Cre-ERT2 cassette is inserted, contains numerous putative transcription factor binding sites. By crossing this line with tdTomato reporter line, we demonstrated that tdTomato expression faithfully recapitulated Fgf10 expression during development. Significantly, Fgf10Ki-v2 mouse is capable of significantly targeting Fgf10Pos cells in the adult lung. Therefore, despite the aforementioned limitations, this new Fgf10Ki-v2 line opens the way for future mechanistic experiments involving the postnatal lung.